Analysis on the accumulation deposits characteristics and formation mechanism of Kangyang landslide in the upper reaches of Yellow River - Gang WEI; Zhiqiang YIN; Yinfei LUO; Liqin WAN; Chunxiao LI (Zhongguo dizhi zaihai yu fangzhi xuebao, 2022)
The development characteristics and formation mechanism of landslides are the basis and premise for further research on landslide prevention and utilization. Therefore, it is necessary to thoroughly study on the development characteristics and formation mechanism of landslides. The Kangyang landslide located at the Qunke-Jianzha Basin in the upper reaches of the Yellow River on the northeastern margin of the Qinghai-Tibet Plateau, it is a typical and super large scale ancient landslide. Its obvious development characteristics and formation mechanism are more representative in the region and has higher academic research value. Combining with the engineering geological drilling data, detailed field investigation and grain size analysis, the author studied the Kangyang landslide morphology characteristics, formation age, grain size of landslide deposit and its formation mechanism. The main conclusions are as follows: 1) Kangyang landslide is a mudstone landslide that occurred in the late Late Pleistocene, with a residual volume of 12.59×108 m3, and the back edge wall is high and upright; 2) Paleoclimate changes may be the key factor triggering the Kangyang landslide. The front edge of the landslide slipped to the north bank of the Yellow River, and the accumulation body may block the Yellow River, which was later cut through by the Yellow River erosion from the middle part. At present, there are still ancient landslide accumulations on the north bank of the Yellow River. 3) The uplift of the plateau and the erosion of the Yellow River may be the background conditions for the occurrence of Kangyang landslide, but the weak sliding zone formed heavy rainfall infiltration and the lateral erosion of the Yellow River may be the main factors triggering the Kangyang landslide.